Respostas

2013-06-11T08:43:43-03:00

a) x² + 10x = 0    

 

Δ==b²-4*a*c

Δ=10²-4*1*0

Δ=100-0

Δ=100

 

x= -b±√Δ  =  -10±√100 = -10±10

      2*a             2*1                2

 

x'= -10+10 = 0

            2

       

x"= -10-10 = -10

           2

 S= { 0, -10 }

 

 

b) x² - 64 = 0  

 

Δ=b²-4*a*c

Δ=0²-4*1*(-64)

Δ=0+256

Δ=256

 

x= -b±√Δ  =  -0±√256 =- 0±16

      2*a             2*1                2

 

x'= 0+16 = 8

           2

       

x"= 0-16 = - 8

           2

 S= { 8, - 8 }

 

 

c)2x²-7 x =0    

 

Δ==b²-4*a*c

Δ=(-7)²-4*2*0

Δ=49-0

Δ=49

 

x= -b±√Δ  =  -7±√49 = -7±7

      2*a             2*2           4

 

x'= -7+7 = 0

         4

       

x"= -7-7 = -14 = -7/2

        4          4 

 S= { 0, -7/2 }

 

 

d)9x²-4=0

 

Δ==b²-4*a*c

Δ=0²-4*1*(-4)

Δ=0+16

Δ=16

 

x= -b±√Δ  =  -0±√16 = -0±4

      2*a             2*9         18

 

x'= 0+4 =

       18

       

x"= 0-4 = -4/18 = -2/9

       18

 

 S={ 2/9, -2/9 }

1 5 1